A randomised, double-blind, placebo-controlled crossover trial of the influence of the HCN channel blocker ivabradine in a healthy volunteer pain model: an enriched population trial. Issue 11 (November 2019) - Lee, Michael C.; Bond, Simon; Wheeler, Daniel; Scholtes, Ingrid; Armstrong, Graham; McNaughton, Peter; Menon, David
Abstract : Abstract: Preclinical studies suggest that type 2 hyperpolarization-activated cyclic nucleotide gated ion channels (HCN2) are necessary for neuropathic pain. This trial assessed the influence of ivabradine, a nonselective HCN channel blocker, on capsaicin-induced hyperalgesia and pain in healthy human subjects. An enriched population comprising subjects who developed >20 cm 2 of punctate hyperalgesia from topical capsaicin (0.5% cream applied onto 9 cm 2 area) was identified. These subjects then received ivabradine (15 mg) or placebo 1 hour before capsaicin application in randomly allocated order in a crossover study. The forearm site for capsaicin alternated with each application of the cream. The interval of time from screening to the first and to the second treatment visits was at least 3 and 5 weeks, respectively, to minimize carryover effects. Fifty-five participants were screened, of which 25 completed at least 1 treatment visit. Intention-to-treat hierarchical analysis revealed no significant effects of the drug on primary trial outcome, defined as a difference in effects of placebo and ivabradine on the area of punctate hyperalgesia (ivabradine − placebo: mean = 3.22 cm 2, 95% confidence interval: = −4.04 to 10.48, P = 0.37). However, ivabradine caused a slowing of heart rate (difference of 10.10 beats per minute [95% confidence interval −6.48 to −13.73; P ‐value <0.0001]). We conclude that ivabradine lacks analgesic effects in the capsaicin pain model at a dose that caused appreciable slowing of heart rate and, hence, is unlikely to prove a useful analgesic in humans. More selective drugs are required to establish a role of HCN2 for pain in humans. Abstract : Supplemental Digital Content is Available in the Text.Ivabradine lacks detectable analgesic effects on experimentally induced pain in human volunteers at a dose that slows heart rate appreciably.